State of Remittance and Balance of Payment in Nepal - Ojha, Gorakh Raj (Economic Literature, 2016)
Foreign employment of Nepali workers is viewed as a potential source of foreign exchange and a way to reduce poverty. This article , on the basis of time series trend of remittance inflow to Nepal , aims at shedding light on the relative importance and contribution of remittance to the BOP of Nepal. It is also tried to spell out problems and remedial measures relating to foreign employment of Nepali workers. Economic Literature, Vol. XI (15-19), June 2013